PENYULUHAN PENCEGAHAN HIPERTENSI DENGAN CERDIK - fara azzahra; Octariana Sofyan; Andi Wijaya; Mexsi Mutia Rissa; Danang Yulianto; Hayatus Sa’adah (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
Hypertension is a condition where the pressure exceeds the normal limit. Uncontrolled high blood pressure can be a risk factor for cardiovascular disease. High blood pressure is still a dominant health problem and requires a good treatment. Counseling to the community of Ledok Timoho village, Muja Muju Umbulharjo Village, Yogyakarta on how to prevent and control hypertension and improve it. The method of activity used in this community service is in the form of counseling on the prevention and control of hypertension, followed by a question and answer discussion, and evaluation of activities using a questionnaire. The results of the implementation of community service showed that there was an increase in the knowledge of PKK mothers about the prevention and control of hypertension in the community from 86.30% to 100%.